2017
DOI: 10.1007/s10865-017-9878-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive step goals and rewards: a longitudinal growth model of daily steps for a smartphone-based walking intervention

Abstract: Adaptive interventions are an emerging class of behavioral interventions that allow for individualized tailoring of intervention components over time to a person's evolving needs. The purpose of this study was to evaluate an adaptive step goal + reward intervention, grounded in Social Cognitive Theory delivered via a smartphone application (Just Walk), using a mixed modeling approach. Participants (N = 20) were overweight (mean BMI = 33.8 ± 6.82 kg/m), sedentary adults (90% female) interested in participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 31 publications
1
115
0
2
Order By: Relevance
“…Four other qualitative studies (of a total of five qualitative studies) [18,56,94,119] provided supportive results, and another qualitative study [98] provided mixed results on PA. For low goals, there were four qualitative and four quantitative studies. All four quantitative studies [115,122,123,137] and four qualitative studies [117,118,126,136] provided supportive effects on PA. Hence, the combined evidence of meta-synthesis and vote counting indicated that goal setting seems to foster PA and that users prefer low over high goals.…”
Section: Goal Settingmentioning
confidence: 91%
See 2 more Smart Citations
“…Four other qualitative studies (of a total of five qualitative studies) [18,56,94,119] provided supportive results, and another qualitative study [98] provided mixed results on PA. For low goals, there were four qualitative and four quantitative studies. All four quantitative studies [115,122,123,137] and four qualitative studies [117,118,126,136] provided supportive effects on PA. Hence, the combined evidence of meta-synthesis and vote counting indicated that goal setting seems to foster PA and that users prefer low over high goals.…”
Section: Goal Settingmentioning
confidence: 91%
“…Goals can be (1) app-set, based on users' PA baseline; (2) user-set, with goals set either independently by users or by following researchers' recommendations; or (3) a mix of app-and user-set, where users choose among app-provided predefined goals. Levels of goal challenges are either higher or lower: (1) higher levels mean more challenging goals are formulated, typically in absolute numbers (e.g., taking 10,000 steps/day), or as challenging increases in PA (e.g., 20% weekly increase in steps/day), or as workout sessions planned by a (virtual) trainer (e.g., running activities, 1 km/session) [16,18,56,94,98,119,128]; (2) lower goals are less challenging and are also formulated as an absolute increase in PA (e.g., 10% weekly increase in steps/day) or as a gradual increase [115,117,118,122,123,126,136,137].…”
Section: Goal Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of changes are an unusual intervention feature within a lifestyle modification program, so participant satisfaction is significant. Previous work has observed that daily novelty in goals is acceptable and efficacious to participants as well (Korinek et al, 2018; Poirier et al, 2016); it may be that novelty in intervention components maintains participant engagement. Participants did express a desire for the automated text messages to be better personalized, so a future iteration of the system might employ more sophisticated tailoring.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive intervention was administered on a smartphone application, in which new physical activity goals were continuously assigned and positive reinforcement was provided for meeting goals. While using the application, participants increased their daily steps by over 2600 per day, as compared to the baseline period in which physical activity goals were not specified (Korinek et al, 2018). Additionally, individual differences in predictors of success on a given day support that an individual-level of tailoring in interventions is justified and may further improve outcomes (Phatak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%